New insights into fibrotic signaling in renal cell carcinoma - Chen, Jiao-Yi; Yiu, Wai-Han; Tang, Patrick Ming-Kuen; Tang, Sydney Chi-Wai (Frontiers in Cell and Developmental Biology, 2023)
Fibrotic signaling plays a pivotal role in the development and progression of solid cancers including renal cell carcinoma (RCC). Intratumoral fibrosis (ITF) and pseudo-capsule (PC) fibrosis are significantly correlated to the disease progression of RCC. Targeting classic fibrotic signaling such as TGF-β signaling and epithelial to mesenchymal transition (EMT) show promising anti-tumor effects both preclinically and clinically. Therefore, better understanding the pathogenic mechanisms of fibrotic signaling in RCC at molecular resolution can facilitate the development of precision therapies against solid cancers. In this review, we systematically summarized the latest updates on the fibrotic signaling, from clinical correlation, molecular mechanisms to their therapeutic strategies for RCC. Importantly, we examined the reported fibrotic signaling on human RCC dataset at transcriptome level with single-cell resolution to assess their translational potential in the clinic.